Reading, Seeing, and Teaching Kafka’s The Metamorphosis in Translation - Mary A Bricker (Studies in 20th & 21st Century Literature, 2026)
“Reading, Seeing, and Teaching Kafka’s The Metamorphosis in Translation” explores teaching Franz Kafka’s The Metamorphosis (Die Verwandlung) at Southern Illinois University Carbondale in English translation as part of German 101b, a second semester introductory German language and culture course. My essay discusses the way in which including Peter Kuper’s 2004 graphic novel adaptation complements Kafka’s novella within our introductory course that serves a broad representation of students with widely divergent academic interests. My paper is informed by visually- and structurally-oriented studies, as well as novella theory and Jungian concepts of transformation. I demonstrate how Kafka’s Metamorphosis can be approached through the intersection of texts that invite a rereading of modernist material that is over a century old.
Keywords: Franz Kafka; The Metamorphosis; Peter Kuper; novella; Carl Jung